2022
DOI: 10.3390/ijms23031593
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Analysis of the 14-3-3 Gene Family in Mango (Mangifera indica L.)

Abstract: Members of the Mi14-3-3 gene family interact with target proteins that are widely involved in plant hormone signal transduction and physiology-related metabolism and play important roles in plant growth, development and stress responses. In this study, 14-3-3s family members are identified by the bioinformatic analysis of the mango (Mangifera indica L.) genome. The gene structures, chromosomal distributions, genetic evolution, and expression patterns of these genes and the physical and chemical properties and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 61 publications
(70 reference statements)
3
15
0
Order By: Relevance
“…In total, 31 putative CO genes were identified from the mango genome (unpublished) ( Xia et al., 2022 ; Zhu et al., 2022 ) using sequences of Arabidopsis CO genes as a reference ( Table 1 ). The conserved domains of the target sequences were evaluated by bioinformatic analysis, and all putative genes were subsequently verified with HMMER and SMART (Simple Modular Architecture Research Tool) online software.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 31 putative CO genes were identified from the mango genome (unpublished) ( Xia et al., 2022 ; Zhu et al., 2022 ) using sequences of Arabidopsis CO genes as a reference ( Table 1 ). The conserved domains of the target sequences were evaluated by bioinformatic analysis, and all putative genes were subsequently verified with HMMER and SMART (Simple Modular Architecture Research Tool) online software.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the Juglandaceae GRF protein family triple structure consists mainly of α-helices, and the phylogenetic relationships of Juglandaceae GRF gene family members can be classified into ε-like and non-ε-like classes, with no amino acid loci detected that are subject to positive selection pressure. Gene structure analysis showed that ε-like GRF genes contain more exons and introns than non-ε-like GRF genes, suggesting that this evolution has driven this diversity, and the above results are similar to those of the mango 14-3-3 family of proteins [ 35 ]. The vast majority of the Juglandaceae GRF family have similar and consistent motif patterns between the ε and non-ε groups, but some members of the non-ε group show considerable variation, containing only Motif1 and Motif2, which may be related to the evolution of individual Juglandaceae species.…”
Section: Discussionmentioning
confidence: 72%
“…Cis-regulatory elements play an important role in the regulation of plant gene expression. The cis-acting element and expression pattern analysis showed that 14-3-3s were involved in hormone and abiotic stress responses in plants (Lyu et al, 2021;Xia et al, 2022;Xie et al, 2022). In this study, we analyzed the stress response-related cis-acting elements in the promoters of BnaGRFs.…”
Section: Discussionmentioning
confidence: 99%
“…A number of 14-3-3 family members have been reported in different plant species; for example, 13 in Arabidopsis (Rosenquist et al, 2001), 8 in rice (Chen et al, 2006), 16 in soybean (Wang et al, 2019), 17 in tobacco (Konagaya et al, 2004), 12 in Populus (Tian et al, 2015), 8 in sweet orange, 15 in cassava (Chang et al, 2020), 11 in grape (Cheng et al, 2018), 17 in wheat (Shao et al, 2021), 10 in Medicago truncatula (Qin et al, 2016), 16 in mango (Xia et al, 2022), 18 in apple (Zuo et al, 2021), 25 in banana (Li et al, 2016), 9 in Citrus sinensis (Lyu et al, 2021), and 21 in Brassica rapa (Chandna et al, 2016). Despite the documentation of 14-3-3 genes in many plant species and their investigation under different stress conditions, little is known about this gene family in rapeseed (Brassica napus) and its diploid progenitor Brassica oleracea.…”
Section: Introductionmentioning
confidence: 99%